Exploring the influence of marine science camps on learners' motivation and dispositions towards scientific inquiry - Hambaze, Nozipiwo (Rhodes University, Faculty of Education, Department of Education, 2020)
For a number of years, it has been observed that learners' motivation towards science has decreased , especially when th ey get to higher grades in secondary school. Strengthening learners' motivation has become a very important area for educators to understand and reflect on. Many studies suggest that inquiry - based learning activities can provide a conducive learning enviro nment and build up learners ' abilities and motivation to learn science beyond the classroom. It is against this backdrop that t his interventionist study s ought to investigate the influence of marine science camps on learners' motivation towards scientific inquiry. The study was informed by Vygotsky 's social constructivist theory and Wenger 's community of practice theory. The participants were 21 grade 10 science learners from seven high schools in the Eastern Cape in South Africa. In order to answer the research questions , data w ere collected through the use of Student Motivation T owards Science Learning (SMTSL) questionnaires prior and post science camp, learner reflection journals and focus group interviews. Excel was used to analyse quantitative data w hereas an inductive - deductive thematic approach was used to analyse the qualitative data.The findin gs of the study revealed that through active participation learners' dispositions shifted and became more positive after the scientific inquiry activity experience at the marine science camp. Furthermore , the findings of the study revealed that as a result of the marine science camp experiences learners were highly motivated to develop their own marine related science projects for the science fairs. Science fairs bear the testimony as one learner did not only co nduct a marine related project for a science fair but was awarded a gold medal at a regional science fair and a silver medal the national fair. The same lea r ne r was awarded an opportunity to present his project in other international fair. Notably also, l earners displayed increase science motivation as a result of participating at the marine science camp. iv This study thus recommends that i n order to enhance scie ntific inquiry among science learners, efforts in developing out - of - school programs not only by th e department of education but also other stakeholders such as universities are needed to inspire and motivate more learners in sciences. Additionally , pure sc ience faculties and social science s should work closely with each other to promote science.
Keywords: Science projects; Marine sciences -- Study and teaching -- South Africa -- Case studies; Active learning; Science camps -- South Africa -- Case studies; Experiential learning; Science -- Study and teaching -- South Africa -- Case studies; Motivation in education -- South Africa -- Case studies